Whooping cough in a renal transplant recipient. Issue 2 (1st March 2016) - Garbiras, M.; Shabaka, A.; Calvo, N.; Martin, L.; Moreno, M.A.; Lopez de la Manzanara, V.; Sanchez‐Fructuoso, A.I.
Abstract: Whooping cough is a respiratory infection with a severity that varies with age, immune status, and probably with other factors such as the degree of exposure and the virulence of the organism. The most frequent microorganism responsible for whooping cough is Bordetella pertussis . We present the case of a 62‐year‐old renal transplant recipient presenting with typical and severe manifestations of whooping cough caused by B. pertussis .